Brachialgia: possible causes of pain (literature review) - D. A. Grishina; N. A. Suponeva; N. V. Belova; D. A. Grozova (Нервно-мышечные болезни, 2019)
This literature review provides a range of neurological and other organic causes of brachialgia. Features of pain syndrome in different medical conditions are described.